Ethical problems in nursing management: The role of codes of ethics - Aitamaa, Elina (Nursing ethics, 2010)
The aim of this study was to identify the ethical problems that nurse managers encounter in their work and the role of codes of ethics in the solutions to these difficulties. The data were collected using a structured questionnaire and analysed statistically. The target sample included all nurse managers in 21 specialized health care or primary health care organizations in two hospital districts in Finland (N = 501; response rate 41%). The most common ethical problems concerned resource allocation as well as providing and developing high quality care. This was the case in different managerial positions as well as in types of organization. Professional codes of ethics were used more often for problems related to patients’ care compared with issues of resource allocation. Nurse managers at middle or strategic management levels used codes of ethics more often than those in charge of a ward. More research is required to investigate ethical decision making in nursing management, especially with regard to problem solving. In addition, new guidelines and continuing education in ethics are important for management personnel.